Evaluation of clinical prediction models (part 2): how to undertake an external validation study - Riley, RD; Archer, L; Snell, KIE; Ensor, J; Dhiman, P; Martin, GP; Bonnett, LJ; Collins, GS (BMJ Publishing Group, 2024)
External validation studies are an important but often neglected part of prediction model research. In this article, the second in a series on model evaluation, Riley and colleagues explain what an external validation study entails and describe the key steps involved, from establishing a high quality dataset to evaluating a model’s predictive performance and clinical usefulness.